[PIN+]: prions beget prions - Liebman, Susan (Henry Stewart Talks, 2008)
Prions are infectious proteins, [PIN+] is a prion of Rnq1, [PIN+] exists as different variants, Prions can affect the stability of other variants of the same prion, or of heterologous prions
Reviewed at 2020/05/01, Archived at 2021/02/25